If it's not what You are looking for type in the equation solver your own equation and let us solve it.
y(5-y)=7y
We move all terms to the left:
y(5-y)-(7y)=0
We add all the numbers together, and all the variables
y(-1y+5)-7y=0
We add all the numbers together, and all the variables
-7y+y(-1y+5)=0
We multiply parentheses
-1y^2-7y+5y=0
We add all the numbers together, and all the variables
-1y^2-2y=0
a = -1; b = -2; c = 0;
Δ = b2-4ac
Δ = -22-4·(-1)·0
Δ = 4
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$y_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$y_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$\sqrt{\Delta}=\sqrt{4}=2$$y_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-2)-2}{2*-1}=\frac{0}{-2} =0 $$y_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-2)+2}{2*-1}=\frac{4}{-2} =-2 $
| 12m-5=11-5 | | 9d=-8+5d | | x^2+4x+188=0 | | 16-2x=2x+14 | | x^2+4+188=0 | | 144=18/x | | -9-2f+10=9-f | | 16t/t-5=14/4 | | 4v-6=v+9 | | X+6=3x-3 | | 2^x+3=4^x-5 | | (-z+37)+(7z-85)=2(4z-41) | | -5m-6=6-3m | | -2(a-2)+5(a+3)=25 | | x=9,x=-3 | | 2=3/4x+5/4 | | 4t=32;t=8 | | 6z+1/9=7z+5/9 | | −8(−8x−6)=−6x−22 | | 5c+2=-c-8 | | 2=3/4r+5/4 | | 5t=t(t-4) | | (-6z+41)+(z+55)=2(-8z+59) | | 2−4x=−36 | | -2t-6=-t | | 9x+6x=7 | | 6-6x+42+7=0 | | 1-9v=-9v+4v+9 | | y/5+4=y/4 | | 5×-3.2=z | | (-s+8)+(7s+2)=2(-6s+23) | | 6s+2-4=10 |